PERIOPERATIVE MANAGEMENT OF HIGH-RISK CARDIOVASCULAR PATIENTS IN ABDOMINAL SURGERY - Anđelković, Ana; Tanasić, Stefan (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: The preparation of cardiovascular patients for different types of surgical interventions represents a challenge in an anesthesiologist’s everyday practice. Its complexity depends on the severity of the underlying disease, the effects of the drug treatment, urgency, and the type of surgical intervention. Different types of scoring systems are available when it comes to the assessment of cardiovascular risk in patients during surgery. One of them, Revised Cardiac Risk Index (RCRI/Lee criteria), stands out due to its comprehensiveness and simplicity, and is thus applied most frequently. Using the example of two patients with cardiovascular disease, the aim of this paper is to show how the risk of perioperative complications can be reduced by applying a multidisciplinary approach, along with an individualized strategy and modern guidelines. Case reports: In the first case, we presented a patient with acute appendicitis. Because of angina pectoris, one month prior to the planned abdominal surgery, Percutaneous Coronary Intervention was performed placing one stent, after which dual antiplatelet drugs were prescribed.A patient with acute cholecystitis is presented in the second case. Coronary artery bypass grafting is planned within a month upon the abdominal surgery, due to a severe form of ischemic cardiomyopathy. Both patients are at high risk of myocardial damage during surgery, the first patient being at high risk of hemorrhage as well. Conclusion: The appropriate balance in the perioperative care of such patients can be achieved by a multidisciplinary approach, as well as by adapting modern guidelines to patients’ individual needs.
Keywords: cardiovascular patient; abdominal surgery; Lee Criteria; myocardial injury